2011
DOI: 10.1007/s11596-011-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

Different optical properties between human hepatocellular carcinoma tissues and non-tumorous hepatic tissues In Vitro

Abstract: There has been an ongoing search for clinically acceptable methods for the accurate, efficient and simple diagnosis and prognosis of hepatocellular carcinoma (HCC). Optical spectroscopy is a technique with potential clinical applications to diagnose cancer diseases. The purpose of this study was to obtain the optical properties of HCC tissues and non-tumorous hepatic tissues and identify the difference between them. A total of 55 tissue samples (HCC tissue, n=38; non-tumorous hepatic tissue, n=17) were surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…3 suggest that the optical properties of tissue types contain the most discriminative information for tissue classification in the VIS wavelength range between 450 nm and 750 nm. These findings are similar to those that have been reported for different ex vivo studies on human liver tissue of tumor patients with primary cancer [14], as well as with liver metastases [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…3 suggest that the optical properties of tissue types contain the most discriminative information for tissue classification in the VIS wavelength range between 450 nm and 750 nm. These findings are similar to those that have been reported for different ex vivo studies on human liver tissue of tumor patients with primary cancer [14], as well as with liver metastases [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
“…Extracted from diffuse reflectance spectra, Nachabé et al [18] have shown that the amount of bile in metastatic tumor tissues is 80% lower than in healthy liver tissue. Although, primary liver cancer cells can produce bile, the diffuse reflectance spectra show comparable results of absorption in the wavelength range between 400 nm and 500 nm with spectra of metastases [14]. Yu et al explain this finding with the presence of an additional chromophore existing mainly in the liver parenchyma called cytochrome P-450 [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations